Dek overexpression in murine epithelia increases overt esophageal squamous cell carcinoma incidence - Matrka, Marie C. (PLoS Genet, 2018)
Esophageal cancer occurs as either squamous cell carcinoma (ESCC) or adenocarcinoma. ESCCs comprise almost 90% of cases worldwide, and recur with a less than 15% five-year survival rate despite available treatments. The identification of new ESCC drivers and therapeutic targets is critical for improving outcomes. Here we report that expression of the human DEK oncogene is strongly upregulated in esophageal SCC based on data in the cancer genome atlas (TCGA). DEK is a chromatin-associated protein with important roles in several nuclear processes including gene transcription, epigenetics, and DNA repair. Our previous data have utilized a murine knockout model to demonstrate that Dek expression is required for oral and esophageal SCC growth. Also, DEK overexpression in human keratinocytes, the cell of origin for SCC, was sufficient to cause hyperplasia in 3D organotypic raft cultures that mimic human skin, thus linking high DEK expression in keratinocytes to oncogenic phenotypes. However, the role of DEK over-expression in ESCC development remains unknown in human cells or genetic mouse models. To define the consequences of Dek overexpression in vivo, we generated and validated a tetracycline responsive Dek transgenic mouse model referred to as Bi-L-Dek. Dek overexpression was induced in the basal keratinocytes of stratified squamous epithelium by crossing Bi-L-Dek mice to keratin 5 tetracycline transactivator (K5-tTA) mice. Conditional transgene expression was validated in the resulting Bi-L-Dek_K5-tTA mice and was suppressed with doxycycline treatment in the tetracycline-off system. The mice were subjected to an established HNSCC and esophageal carcinogenesis protocol using the chemical carcinogen 4-nitroquinoline 1-oxide (4NQO). Dek overexpression stimulated gross esophageal tumor development, when compared to doxycycline treated control mice. Furthermore, high Dek expression caused a trend toward esophageal hyperplasia in 4NQO treated mice. Taken together, these data demonstrate that Dek overexpression in the cell of origin for SCC is sufficient to promote esophageal SCC development in vivo.